2022
DOI: 10.1177/1356336x221084516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a two-stage physical education teacher education programme on preservice teachers’ specialised content knowledge and students’ game-play in a student-centred Sport Education-Step Game approach

Abstract: This study aimed to examine the effects of a physical education teacher education programme on (a) preservice teachers’ (PSTs') specialised content knowledge (SCK), and (b) the game-play development of their students, during a student-centred Sport Education-Step Game Approach (SE-SGA) unit. Three PSTs selected by convenience sampling (22–24 years old), their 60 eighth-grade students (three classes: 38 boys, 22 girls, Mage = 13.3), and a mentoring team (one teacher educator, one university supervisor, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…As mentioned above, the selected investigations were classified into three categories: Pedagogical Content Knowledge in School Physical Education, Pedagogical Content Knowledge in School Sports and Pedagogical Content Knowledge in Physical Education Teacher Training Programs; in Table 2 they are organized according to these categories and the authors who refer to them and, subsequently, a description of each one is presented. Fierro, Feu, et al, 2018;Almonacid-Fierro, Merellano-Navarro, et al, 2018;Ayvazo & Ward, 2011;Castejón Oliva & Fuentes Guerra, 2017;Chang et al, 2020;Ward, 2013) Pedagogical knowledge of the content in School Sport (Araújo et al, 2017;He et al, 2022;Iserbyt et al, 2016Iserbyt et al, , 2017Iserbyt et al, , 2020Kim & Ko, 2020;Sinelnikov et al, 2016;Ward et al, 2015) Pedagogical knowledge of content in physical education teacher training programs (Backman et al, 2019;Backman & Barker, 2020;Cañadas et al, 2019;Dervent et al, 2020;Farias et al, 2022;García-Rico et al, 2021;Herold, 2019;Herold & Waring, 2017;Le Paven et al, 2021;Marcon et al, 2012;Marquis & Metzler, 2017;Meier, 2020Meier, , 2021Montoya-Grisales et al, 2022;Musard et al, 2022;Mustell et al, 2022;Sutherland et al, 2016)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the selected investigations were classified into three categories: Pedagogical Content Knowledge in School Physical Education, Pedagogical Content Knowledge in School Sports and Pedagogical Content Knowledge in Physical Education Teacher Training Programs; in Table 2 they are organized according to these categories and the authors who refer to them and, subsequently, a description of each one is presented. Fierro, Feu, et al, 2018;Almonacid-Fierro, Merellano-Navarro, et al, 2018;Ayvazo & Ward, 2011;Castejón Oliva & Fuentes Guerra, 2017;Chang et al, 2020;Ward, 2013) Pedagogical knowledge of the content in School Sport (Araújo et al, 2017;He et al, 2022;Iserbyt et al, 2016Iserbyt et al, , 2017Iserbyt et al, , 2020Kim & Ko, 2020;Sinelnikov et al, 2016;Ward et al, 2015) Pedagogical knowledge of content in physical education teacher training programs (Backman et al, 2019;Backman & Barker, 2020;Cañadas et al, 2019;Dervent et al, 2020;Farias et al, 2022;García-Rico et al, 2021;Herold, 2019;Herold & Waring, 2017;Le Paven et al, 2021;Marcon et al, 2012;Marquis & Metzler, 2017;Meier, 2020Meier, , 2021Montoya-Grisales et al, 2022;Musard et al, 2022;Mustell et al, 2022;Sutherland et al, 2016)…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies show that CK limitations have an adverse effect on PCK (Herold & Waring, 2017), given that, as reported by Le Paven et al ( 2021), to access a suitable PCK, a deep knowledge of the contents is required; however, it has also been shown that CK by itself is not enough if you want to teach attractive lessons (Herold & Waring, 2017), in addition, that it is necessary to trust the sequence of the class, facilitate the approach to the contents and help process the lived experience (Sutherland et al, 2016). Preservice teachers can develop their CK based on their participation in training protocols tailored to the development of CCK and SCK, and specific pedagogies of Learner-Centered Model-Based Practice (Farias et al, 2022) Thus, achieving an effective PCK in initial training implies that the teacher in training evaluates where the group he is in charge is at, that is, that he has knowledge of the student, and that he is capable of interpreting his actions and reactions in class (Backman & Barker, 2020;Sutherland et al, 2016), as well as being able to adapt to the conditions of the context (Meier, 2020) and choose which models or approaches to use (Mustell et al, 2022). That is why, the programs that train PE teachers must emphasize the acquisition of skills in aspects such as: the execution of contents and teaching (Marquis & Metzler, 2017), especially from school practices (Herold, 2019); in learning from university service (García-Rico et al, 2021); the use of the joint action framework in didactics (Musard et al, 2022); in knowing how to use the game as a didactic resource and as teaching content (Cañadas et al, 2019) and, in valuing the CK of the movement from a constructivist perspective (Backman et al, 2019).…”
Section: Pedagogical Knowledge Of Content In Physical Education Teach...mentioning
confidence: 99%
“…Therefore, interventions through hybridizations can help in the improvement in students’ motor skills and game performance. Previous studies reported the positive effects of SE, IGCM, and SGA in isolation on students’ motor learning [ 45 , 60 , 61 ]. SE aims to cultivate capable, educated, enthusiastic athletes by adopting more democratic and inclusive teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, such research in PETE has translated into clearly identifiable practises. For example, in Oporto, the practical content is delivered in a combined approach through "pedagogical models" (e.g., SEM) and the "pedagogical content knowledge" (e.g., step-game-approach) (88). Furthermore, longitudinal research has been carried out to uncover the professional development of student-teachers.…”
Section: Physical Education Teacher Education (Pete)mentioning
confidence: 99%